2022
DOI: 10.21203/rs.3.rs-1592253/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gait training with a wearable curara ® robot during stroke rehabilitation: a randomized parallel-group trial

Abstract: Background: Recently, robot-assisted gait training (RAGT) has been applied widely to individuals with stroke to regain and improve walking ability. We have developed a non-exoskeleton rehabilitation robot, “curara®,” and examined its immediate effect in patients with spinocerebellar degeneration and stroke, but its rehabilitative effect has not been clarified. The purpose of this study was to examine the effect of curara® on gait training in stroke patients.Methods: Forty stroke patients were enrolled in this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Also, the TUG outcome was signi cantly improved only in the robotic group (9). In the study of Miyagawa et al (2023), despite improvement in both groups, no signi cant differences were observed between the two groups in 6MWT, TUG, and BBS outcomes (25). Comparing the results of the present research with the aforementioned studies and the lack of consistency in some results shows that depending on the difference in the parameters affecting the research, such as the type of method, the type of robot, the phase of the disease, the number and duration of treatment sessions, etc., we will see different results.…”
Section: Discussionmentioning
confidence: 91%
“…Also, the TUG outcome was signi cantly improved only in the robotic group (9). In the study of Miyagawa et al (2023), despite improvement in both groups, no signi cant differences were observed between the two groups in 6MWT, TUG, and BBS outcomes (25). Comparing the results of the present research with the aforementioned studies and the lack of consistency in some results shows that depending on the difference in the parameters affecting the research, such as the type of method, the type of robot, the phase of the disease, the number and duration of treatment sessions, etc., we will see different results.…”
Section: Discussionmentioning
confidence: 91%
“…The motion process for the same subject shows almost no variation because of the use of Lokomat's passive movement mode and the xed walking speed. Conventional methods of gait analysis, such as analyzing the step frequency, speed, and stride length [23], are not applicable in this context. Therefore, we analyzed the angle and torque data during the training process.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…With stroke, patients often have different degrees of motor impairment, making it difficult to walk and reintegrate into society and negatively affecting their physical and mental health (7). There are few studies on the social alienation of patients with stroke, most of which focus on the negative emotions and motor impairment caused by stroke (8,9). Therefore, it is essential to investigate the social alienation of patients with stroke and explore its potential mechanism to help patients better adapt to society.…”
Section: Open Access Edited Bymentioning
confidence: 99%